The Effect of Temperature on the Accuracy of Postmortem Interval Estimation Based on the Larval Growth of the Green Bottle Fly Lucilia sericata Using Isomegalen Diagrams - Sara Elhammi; Nawal Mahfoud; Hamida Jbr (AlQalam Journal of Medical and Applied Sciences, 2026)
Forensic entomology provides essential tools for estimating the post-mortem interval (PMI), particularly when traditional pathological methods are limited. This study investigates the larval development of Lucilia sericata (green bottle fly) under realistic environmental conditions to evaluate the influence of temperature on PMI estimation. Two rabbit carcasses were monitored during February 2025, with daily temperatures ranging from 14.65°C to 15.5°C. Larvae were collected, measured, and analyzed using isomegalen charts to determine developmental durations. Results indicated that even a minor difference of 1°C between sampling periods significantly affected total larval development, with Sample A requiring 235 hours and Sample B 198 hours to reach maximum lengths. The hatching period remained relatively stable (30–32 hours), suggesting early developmental stages are less sensitive to small temperature variations. A clear difference was observed between temperature conditions based on larval growth patterns derived from the isomegalen chart. The findings indicate that relying on local temperature data, larval measurements, and population-specific developmental references plays a crucial role in improving the accuracy of PMI estimation. Incorporating precise environmental and experimental data enhances the reliability of forensic entomology as an effective tool in legal investigations.